Maritime medicine in Ukraine: the present-day state and some lines of its reforming - Gozhenko, A.I. (Актуальні проблеми транспортної медицини, 2011)
Examined the role of the Ukrainian Research Institute of Transport Medicine in the structure of marine medicine in Ukraine. A scheme for reform of maritime medicine in Ukraine based on scientific research experts from the Instituteof Transport Medicine. Розглянуто роль Українського НДІ медицини транспорту в структурі морської медицини Україну. Запропоновано схему реформування морської медицини в Україну на основі наукових розробок фахівців Інституту медицини транспорту. Рассмотрена роль Украинского НИИ медицины транспорта в структуре морской медицины Украины. Предложена схема реформирования морской медицины в Украине на основе научных разработок специалистов Института медицины транспорта.